Strengthening SMA/MA Students' Language Attitudes Towards Indonesian Through the Word Spinner Application - Ridaningsih; Jaja Wilsa; Dede Endang Mascita (PT Inovasi Pratama Internasional, 2024)
The main problem using Indonesian was n't in accordance with linguistic rules so that students' s language did not reflect the desired language attitudes. The data obtained becomes material for preparing further strengthening plans which are developed to be media-based. After being validated by material and media experts, the language attitude strengthening model is applied to students using Android cellphones and laptop devices connected to the network. The aim of this research explains the design and implementation of strengthening student's language attitudes towards Indonesian through the medium of the word spinner application. This research uses a qualitative approach with the research method and development of the ADDIE model. Data collection methods through test and non-test instruments. The average validation data by material experts and media experts received a score of 84.45%, which means it is very feasible to apply, while the average error rate in analyzing by SMA and MA respondents is 33.5%, which means students are quite careful in understanding the instrument for strengthening language attitudes. It is also meaningful that this application is suitable for implementation in schools with its main advantage being that it teaches students with learning outcomes that meet 3 aspects of language attitudes, namely cognitive, affective and conative. T he ease of teaching vocabulary and its application in sentences so that students fully understand the language properly and correctly. The limitations of this application require technical requirements, namely the availability of computers/laptops and Android cellphones used by teachers and students who are connected to the internet.